Luiz F. G. Labouriau and the dawn of seed science in Brazil - Daibes, L. Felipe [UNESP]; Borghetti, Fabian; Ferreira, Alfredo G. (Cambridge University Press (CUP), 2021)
Luiz Fernando Gouvêa Labouriau (1921-1996) was a pioneer plant biologist who made significant contributions to plant physiology, mostly by bringing seed germination into a thermobiological context. His studies have set the foundations of seed science in Brazil and keep inspiring researchers until now.
Keywords: cardinal temperature; germination rate; homage; plant physiology; thermal biology